Evaluación y valoración cuantitativa de la masa arbórea de una hectárea de bosque secundario, Fundo Pabloyacu - Pinto Flores, Víctor Alan (2009)
Recent data evidence that the destruction ofthe primary Forests has been come together with for the expansion of the secondary forests. The studies also evidence that the secondary forests Are capable of providing sorne of the cost-reducing and ecological services of the primary forests. This has led to a new strategy to increase the value of the secondary forests for farmers and cattle farmers, for the sake of leading to them to preserve these forests indefinitely, or at least to delay his reconversion to other uses. The objective ofthis study becomes of contributing toa coherent strategy to accomplish the poten ti al of the secondary forests. Important areas under secondary forest at lots of children and big producers exist and than through interventions technologies and he can increment the area and the costreducing and ecological value of secondary forests significantly of policy and, consequently, the period for which these are chatted. Also he makes a date that the secondary forests are highly variable in his ecological characteristics and in terms of objectives and his proprietors' resources. Therefore it's probable that the required interventions be highly variable. An analysis of the dynamics of the Secondary forests can help to address the interventions to those aerial with the highest probability of impact. The secondary analysis of the socioeconomic aspects of the dynamics of forest is based on the progressive change in the time of sorne characteristics of aerial of agricultura! frontier. We do the distinction between two different trajectories: That one followed by colonists and the one belonging to indigenous communities. A third category of accidental circumstances, such like military conflicts and litigation, also they can lead to the creation of secondary forests. He backs up the options of handling for forests they classify of agreement to his resourceful request ( capital, land, hand of work and capability related to management ) and the time passing to obtain a product proving to be four groups: Fallows improved of short cycle, fallows enriched of half a cycle forest of production of half a cycle to length and forests of conservation. The characteristics of every category of producers and his secondary forests are contrasted with the characteristics of the options of handling where the probability of adoption is her but tall. · Next they identify the general categories of interventions of policy adapted for each producer's category, being: Policies related to the marketing of products of the secondary forest, reforms of the legislation and policies that they allow the producers grabbing the value ofthe environmental services that they supply the secondary forests. We concluded emphasizing the importance of a conceptual dynamic frame for the development of a strategy for secondary forests, that it allows preventing from degradation the I refuse, contrary to revert this after I happen. The conceptual frame that shows up also enables the analysis of secondary forests like a comprehensive part of the system of production of the farmer. Finally it is emphasized that the principal contribution of this exercise is the conceptual frame. Results are merely indicative and need to be proven with empiric data.